2020
DOI: 10.3168/jds.2019-17165
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and angiotensin-converting enzyme inhibitory activity of fermented milk with different culture combinations

Abstract: This study investigated the effects of Lactobacillus plantarum (Lp) and Bifidobacterium animalis ssp. lactis (Ba) in co-cultures with Streptococcus thermophilus (St) on changes in the acidification profile, proteolytic activity, peptide production, in vitro antioxidant activity, and angiotensin-converting enzyme (ACE) inhibitory properties of fermented milks during 21 d of storage at 4°C. The pH values and proteolysis in all batches showed a gradual decrease and increase during storage, respectively. The ACE-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 58 publications
(65 reference statements)
2
26
0
Order By: Relevance
“…DPPH and ABTS radicals were widely used to evaluate the antioxidant ability of polysaccharides. 22,28,29 As shown in Fig. 4A, the scavenging activity of crude polysaccharides DAE-PTXP, As shown in Fig.…”
Section: In Vitro Antioxidant Activity Of Ptxps and Puried Ptxpsmentioning
confidence: 82%
“…DPPH and ABTS radicals were widely used to evaluate the antioxidant ability of polysaccharides. 22,28,29 As shown in Fig. 4A, the scavenging activity of crude polysaccharides DAE-PTXP, As shown in Fig.…”
Section: In Vitro Antioxidant Activity Of Ptxps and Puried Ptxpsmentioning
confidence: 82%
“…25 Furthermore, it is known that the peptides and amino acid released by the proteolytic processes can positively influence the nutritional characteristics of the final product. 26 The κ-casein polypeptides corresponding to the spots KA, KB, and KC contain the sequence YIPIQYVLSR that correspond to the casoxin C, a bioactive compound that acts mainly as an opioid antagonist and is obtained from the digestion of κ-casein. In particular, this peptide has shown its activity against the suppressive effect of DAGO, a μ-opioid agonist evoking the contraction of ileum with rapid and slow components.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have found that the proteolytic enzymes released from LAB are active during the fermentation process and in the fermented dairy products 24 and also that the choice of the starter culture can influence the proteolysis characteristics 25 . Furthermore, it is known that the peptides and amino acid released by the proteolytic processes can positively influence the nutritional characteristics of the final product 26 …”
Section: Resultsmentioning
confidence: 99%
“…A study investigating the effect of L. plantarum and B. animalis subsp. lactis in co‐cultures with S. thermophilus on different functional characteristics of fermented milk reported significantly higher DPPH radical scavenging activity, hydroxyl radical scavenging activity, and total antioxidant activity in milk compared to the milk fermented by only S. thermophilus (Li, Tang, et al., 2020; Li, Wu, et al., 2020). Skimmed milk fermented by L. plantarum WW has been shown to regulate lipid metabolism and cholesterols levels in rats fed a high‐fat diet (Li, Tang, et al., 2020; Li, Wu, et al., 2020).…”
Section: Health Benefits/physiological Effects Of Probiotic Dairy Productsmentioning
confidence: 99%